The silent cries of sexual abuse and a new hope - Repič Slavič, Tanja (knjige, 2025)
The book THE SILENT CRIES OF SEXUAL ABUSE AND A NEW HOPE includes most of the known theories and studies in the field of sexual abuse, which are complemented by and placed in the context of relational family therapy with sexually abused persons. Special attention is given to the clarification and understanding of the consequences of sexual abuse in the following four areas: body, sexuality, self-image and family of origin. The main part of the book considers sexual abuse in light of relational family therapy, describing the characteristics of the mentioned therapy and the process and stages of working through a traumatic event. The theoretical passages are intertwined with statements of sexually abused persons obtained in a therapeutic process. Some refer to the state before the therapeutic process, others to the experiences after it. The essential changes in participants confirm that the use of the relational family therapy approach in cases of sexual abuse is justified since it is precisely the new, more pleasant experiences in general and more positive experiences of sexuality and one’s body plus a different attitude towards oneself and others that give new hope to everyone who has lived through sexual abuse.
Keywords: elektronske knjige; psihične travme; psihosomatika; relacijska družinska terapija; samopodoba; Spolna zloraba; spolnost; zdravstvene težave